Protein phosphorylation pattern in the immune cells of leprosy affected individuals - Karuna Devi Sagili,1 Renuka Raju,1 Venkat Rami Reddy,2 Anandaraj M.P.J.S,1 Sujai Suneetha,3 Lavanya Moses Suneetha.3 (The Journal of Infection in Developing Countries, 2008)
Background: Leprosy is an infectious disease in which the susceptibility to the pathogen Mycobacterium leprae and the clinical manifestations are attributed to host immune cell response. Receptor mediated events and signalling in the immune cells are mediated by protein phosphorylation. The main signalling pathways and protein kinases known to be involved in the regulation of immune cells are cAMP dependent kinases, calcium/calmodulin dependent kinases, protein kinase C and mitogen activatedprotein kinases. The cumulative consequence of alterations in signalling pathways can be evaluated by intrinsic cellular protein phosphorylation by ã-P32 ATP. The present study was designed to assess the protein phosphorylation in the immune cells of leprosy patients as compared with normal individuals.Methodology: Lymphocyte protein phosphorylation was conducted in 15 leprosy patients and 9 normal individuals. Protein phosphorylation of lymphocytes was carried out in the presence/absence of protein kinase modulators. The phosphorylation patterns were documented and analysed consequent to SDS-PAGE, staining, destaining, drying and autoradiography.Results: The major phosphorylated proteins in lymphocytes were of molecular weights 20-22, 24-29, 30-35, 43, 46-50 and 66- 68 kDa. In general, the major phosphorylated proteins were similar in the controls and in the patients. The phosphorylatability of these proteins varied with different modulators. Variations in the phosphorylation pattern were observed in 25% of the leprosy patients where there was a decrease of the 66kDa protein and a decrease of 20-22kDa protein phosphorylation.Conclusion: The observed alterations in the protein phosphorylation pattern could be due to alteration in kinases and/or their substrates or due to the effect of M. leprae on immune cells.